Modelling of ductile fracture in single point incremental forming using a modified GTN model - Gatea, Shakir; Ou, Hengan; Lu, Bin; McCartney, Graham (Elsevier, 2017)
Understanding the deformation and failure mechanisms in single point incremental forming (SPIF) is of great importance for achieving improved formability. Furthermore, there will be added benefits for more in depth evaluation of the effect of localised deformation to the fracture mechanism in SPIF. Although extensive research has been carried out in recent years, questions still remain on the shear and particularly its effect to the formability in SPIF processes. In this work, a modified Gurson–Tvergaard-Needleman (GTN) damage model was developed with the consideration of shear to predict ductile fracture in the SPIF process due to void nucleation and coalescence with results compared with original GTN model in SPIF. A combined approach of experimental testing and SPIF processing was used to validate finite element results of the shear modified Gurson–Tvergaard-Needleman damage model. The results showed that the shear modified GTN model improved the modelling accuracy of fracture over the original GTN model under shear loading conditions. Furthermore, the shear plays a role under meridional tensile stress to accelerate fracture propagation in SPIF processes.